2015
DOI: 10.1177/0960327115578743
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic use of inhaled methoxyflurane

Abstract: Methoxyflurane is a volatile, halogenated analgesic, self-administered in a controlled low dose from the Penthrox® inhaler for short-term pain relief. It was formerly used in significantly higher doses to produce anaesthesia, when it caused a specific type of dose-related renal tubular damage. The pathogenesis of the renal damage and clinical use of methoxyflurane are discussed here with evidence that a low but effective analgesic dose is not associated with the risk of renal adve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 54 publications
1
30
0
1
Order By: Relevance
“…Similarly, in patients receiving methoxyflurane as procedural analgesia for bone marrow biopsy, blood analysis of urea and electrolytes was no different between those patients receiving methoxyflurane and those receiving placebo [35]. These observations are consistent with the findings of Dayan [17], who reviewed laboratory and clinical data relevant to nephrotoxicity and methoxyflurane and concluded that low-dose use of methoxyflurane for analgesia has a large safety margin (at least 2.7- to 8-fold based on methoxyflurane MAC-hours or serum fluoride level) and does not carry a risk of causing renal dysfunction or damage. Furthermore, over 5 million doses of Penthrox have been sold with no pharmacovigilance-related trends suggesting nephrotoxicity.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Similarly, in patients receiving methoxyflurane as procedural analgesia for bone marrow biopsy, blood analysis of urea and electrolytes was no different between those patients receiving methoxyflurane and those receiving placebo [35]. These observations are consistent with the findings of Dayan [17], who reviewed laboratory and clinical data relevant to nephrotoxicity and methoxyflurane and concluded that low-dose use of methoxyflurane for analgesia has a large safety margin (at least 2.7- to 8-fold based on methoxyflurane MAC-hours or serum fluoride level) and does not carry a risk of causing renal dysfunction or damage. Furthermore, over 5 million doses of Penthrox have been sold with no pharmacovigilance-related trends suggesting nephrotoxicity.…”
Section: Discussionsupporting
confidence: 75%
“…In a much larger controlled observational study of patients receiving analgesia during ambulance transport, comparing 17,629 patients receiving methoxyflurane with 118,141 patients not receiving methoxyflurane, no link between methoxyflurane use for emergency analgesia and renal disease (or hepatic disease) was observed [16]. Whilst the literature and post-marketing surveillance in Australia suggest that nephrotoxicity and/or hepatotoxicity of methoxyflurane at analgesic doses is not a risk [16, 17], a study is underway in the UK to understand hepatotoxicity in the pre-hospital and ED settings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…-a case series of use in the prehospital setting noted that it exhibited excellent analgesic properties in much lower doses than those used for anaesthesia (Cousins and Mazze, 1973). The upper limit of safety for methoxyflurane has been determined to be 2 MAC (minimal alveolar concentration)-hours (Dayan, 2016). Doses below 2 MAC-hours have not been associated with nephrotoxicity.…”
Section: Methoxyflurane (Penthrox ® )mentioning
confidence: 99%